Physical changes due to a deforming porous media - a finite element solution - Sukirman, Yahya; Ismail, Raihan; Samsuri, Ariffin (2004)
This paper discusses a finite element solution to investigate the physical changes due to the deforming porous media. The mathematical model was derived based on Biot's self-consistent theory, which describes a fully compled governing equation system for a multiphase flow in a three dimensional reservoir system. It consists of the equilibrium and continuity equations for oil, gas and water-phases. An elastoplastic reservoir rock model based on the Mohr Coulomb yield criteria was used for simulating the deformation behaviour of the reservoir. The compressibility factors are calculated based on the unknowns solved in each time step. Finally, the recent values of porosity and permeability are calculated for various types of reservoir rocks.